EKONOMI SYARIAH: DEFINISI, KONSEP DAN MANFAAT - Nandra, Andre Syah; Kurniawan, Yova Dwi (STAI Darul Qalam Tangerang, 2024)
Sharia economics is an economic system based on the values and principles of Islamic teachings. This system is run based on the principles of justice, togetherness, equity, and benefits in accordance with Islamic law. Sharia economics aims to achieve stability in the welfare of the ummah without benefiting one party and hindering other economic activities. In this system, economic transactions are carried out based on sharia principles, such as not using riba and prohibiting transactions that contain elements of fraud or gharar. Sharia economics also pays attention to corporate social responsibility in accordance with sharia, such as the disclosure of corporate social responsibility through the Ismic Social Reporting (ISR) Index